Large scale synthesis of hexagonal boron nitride nanosheets and their use in thermally conductive polyethylene nanocomposites - Mehamed Ali (14778292) (2023)
Despite their isostructural similarity to graphene, large-scale preparation of hexagonal boron nitride nanosheets (hBNNs) has been challenging, mainly due to their strong interlayer interactions initiated by the electronegativity difference in their elemental components. In this study, a large-scale synthesis of hBNNs via a ball milling (BM) technique is reported. The hBN exfoliation was optimized by analyzing the effect of the ball milling process parameters (ball to powder ratio, speed, and time) on the quality and yield of hBNNs. hBNNs prepared at the optimum milling conditions (10:1 ball to powder ratio, 250 rpm rotation speed, and 1.5 hours) were examined in terms of yield, stability, structure, and surface chemistry. The yield of hBNNs was significantly high and reached 38% and 60% at 30 minutes and 4.5 hours milling times, respectively. hBNNs prepared at the optimum milling conditions were utilized to fabricate thermally conductive linear low-density polyethylene (LLDPE) nanocomposites. The ultimate application of these nanocomposites is replacing metal evaporators in multi-effect distillation desalination. Therefore, it is a prerequisite to have high thermal conductivity and is essential to have enhanced mechanical durability, thermal stability, and wettability. Thus, the performance of these nanocomposites and conventional composites containing bulk hBN were analyzed in terms of processability, thermal conductivity (κ), and mechanical properties. Finally, a mitigation method to alleviate BM-induced defects and amorphizations was proposed and investigated. This treatment was essential in alleviating hBNNs defects and enhancing the thermo-mechanical properties of LLDPE nanocomposites, making them excellent candidates for heat exchanger applications. Other Information Published in: International Journal of Energy Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/er.7149